Analisis Unsur Fisik dan Batin pada Puisi Aku Kangen 1, Aku Kangen 2, Aku Kangen 3 dan Menunggu Bunga Karya Heri Isnaini, Montase: Serpihan Sajak, Pustaka Humaniora (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research aims to analyze the physical and mental elements in the poems "Aku Kangen 1", "Aku Kangen 2", "Aku Kangen 3" and "Waiting for Flowers" by Heri Isnaini which are contained in the anthology Montase: Serpihan Srêm published by Pustaka Humaniora. The physical elements of poetry include diction, rhythm, imagery, and grammar, while the inner elements include themes, tone, atmosphere, and mandates. This study applies a structural approach with a qualitative descriptive method, which focuses on text analysis as the main focus. The results of the analysis show that these poems use simple but highly emotionally charged language, as well as visual imagery and deep feelings in describing longing and waiting. Certain typography and repetition structures reinforce the dramatic effect and musicality of the poem. From the inner side, the main themes that emerge are longing, loneliness, and hope for encounters, which are conveyed in a melancholy tone and a calm, reflective atmosphere. The implied message encourages the reader to reflect on the meaning of presence, loss, and hope in everyday life. This research confirms Heri Isnaini's ability to unite form and meaning poetically, as well as his contribution to contemporary Indonesian poetry.